Immune responses upon in ovo HVT-IBD vaccination vary between different chicken lines. (November 2019) - Dobner, Marina; Auerbach, Monika; Mundt, Egbert; Preisinger, Rudolf; Icken, Wiebke; Rautenschlein, Silke
Abstract: The genotype of chickens is assumed to be associated with variable immune responses. In this study a modern, moderate performing dual-purpose chicken line (DT) was compared with a high-performing layer-type (LT) as well as a broiler-type (BT) chicken line. One group of each genotype was vaccinated in ovo with a recombinant herpesvirus of turkeys expressing the virus protein VP2 of the infectious bursal disease virus (HVT-IBD) while one group of each genotype was left HVT-IBD unvaccinated (control group). Genotype associated differences in innate and adapted immune responses between the groups were determined over five weeks post hatch. HVT-IBD vaccination significantly enhanced humoral immune responses against subsequently applied live vaccines compared to non-HVT-IBD vaccinated groups at some of the investigated time points ( P  < 0.05). In addition HVT-IBD vaccination had depending on the genotype a significant impact on splenic macrophage as well as bursal CD4 + T-cell numbers ( P  < 0.05). On the other hand, the detectable genotype influence on Interferon (IFN) γ and nitric oxide (NO) release of ex vivo stimulated spleen cells was independent of HVT-IBD vaccination. The results of our study suggest considering a genotype specific vaccination regime in the field. Highlights: HVT-IBD vaccination influences humoral immune responses against other vaccines. The number of germinal centers in the spleen differs between chicken genotypes and increases after HVT-IBD vaccination. BT chickens show more vigorous immune responses during the first 35 dph compared to LT and DT chickens.